Dynamic Balancing of Isoprene Carbon Sources Reflects Photosynthetic and Photorespiratory Responses to Temperature Stress . Issue 4 (15th October 2014) - Jardine, Kolby; Chambers, Jeffrey; Alves, Eliane G.; Teixeira, Andrea; Garcia, Sabrina; Holm, Jennifer; Higuchi, Niro; Manzi, Antonio; Abrell, Leif; Fuentes, Jose D.; Nielsen, Lars K.; Torn, Margaret S.; et al.
Abstract : Uncoupling between photosynthesis and isoprene emissions with temperature reflects the differential temperature sensitivities of photosynthesis and photorespiration . Abstract: The volatile gas isoprene is emitted in teragrams per annum quantities from the terrestrial biosphere and exerts a large effect on atmospheric chemistry. Isoprene is made primarily from recently fixed photosynthate; however, alternate carbon sources play an important role, particularly when photosynthate is limiting. We examined the relative contribution of these alternate carbon sources under changes in light and temperature, the two environmental conditions that have the strongest influence over isoprene emission. Using a novel real-time analytical approach that allowed us to examine dynamic changes in carbon sources, we observed that relative contributions do not change as a function of light intensity. We found that the classical uncoupling of isoprene emission from net photosynthesis at elevated leaf temperatures is associated with an increased contribution of alternate carbon. We also observed a rapid compensatory response where alternate carbon sources compensated for transient decreases in recently fixed carbon during thermal ramping, thereby maintaining overall increases in isoprene production rates at high temperatures. Photorespiration is known to contribute to the decline in net photosynthesis at high leaf temperatures. A reduction in the temperature at which the contribution of alternate carbon sources increased was observed under photorespiratory conditions, while photosynthetic conditions increased this temperature. Feeding [2- 13 C]glycine (a photorespiratory intermediate) stimulated emissions of [ 13 C1–5 ]isoprene and 13 CO2, supporting the possibility that photorespiration can provide an alternate source of carbon for isoprene synthesis. Our observations have important implications for establishing improved mechanistic predictions of isoprene emissions and primary carbon metabolism, particularly under the predicted increases in future global temperatures.